2021
DOI: 10.1177/19401612211050889
|View full text |Cite
|
Sign up to set email alerts
|

Messaging “en Español”: The Impact of Spanish Language on Linked Fate Among Bilingual Latinos

Abstract: While the number of U.S. residents who speak non-English languages at home is on the rise, little is known about the sociopolitical implications of exposure to minority languages among multilingual speakers in the United States. This study analyzes whether exposure to Spanish, a U.S. minority language, impacts perceptions of linked fate among bilingual Latinos, and if so, whether the consumption of ethnic media amplifies this effect. Through a population-based survey experiment among bilingual Latinos, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Linked fate is a specific form of group identity that has been particularly useful in explaining why racial and ethnic minorities will often make political decisions based on the collective interests of their racial or ethnic group (Dawson Michael 1994). While Dawson Michael’s (1994) linked fate theory was originally developed specifically for the African American experience in the US, scholars have found that although the mechanisms that drive linked fate may be different for Latinos (Sanchez and Masuoka 2010; Sanchez et al 2019; Gomez-Aguinaga 2021 a ), linked fate influences Latino political behaviour (Schildkraut 2013; Bejarano et al 2021). We rely on this particular from of group identity in our analysis given the advantage it has of being “a sophisticated and parsimonious alternative” to the operationalization of racial group consciousness (McClain et al 2009).…”
Section: Group Identity and Issue Saliencementioning
confidence: 99%
“…Linked fate is a specific form of group identity that has been particularly useful in explaining why racial and ethnic minorities will often make political decisions based on the collective interests of their racial or ethnic group (Dawson Michael 1994). While Dawson Michael’s (1994) linked fate theory was originally developed specifically for the African American experience in the US, scholars have found that although the mechanisms that drive linked fate may be different for Latinos (Sanchez and Masuoka 2010; Sanchez et al 2019; Gomez-Aguinaga 2021 a ), linked fate influences Latino political behaviour (Schildkraut 2013; Bejarano et al 2021). We rely on this particular from of group identity in our analysis given the advantage it has of being “a sophisticated and parsimonious alternative” to the operationalization of racial group consciousness (McClain et al 2009).…”
Section: Group Identity and Issue Saliencementioning
confidence: 99%
“…Pérez & Tavits, 2022; E. O. Pérez & Tavits, 2019) and of exposure to the minority language on the media (Darr et al, 2020;Gomez-Aguinaga, 2021). These works are helpful to develop theories about the effects of the MLR; yet, we expect the state's direct intervention, as it is the case in the MLR, to trigger separate effects, especially in conflictual settings.…”
Section: Introductionmentioning
confidence: 99%